The 100 thing challenge eaudiobook How i got rid of almost everything, remade my life, and regained my soul. - Bruno, David (Tantor Media, 2020)
In The 100 Thing Challenge Dave Bruno relates how he remade his life and regained his soul by getting rid of almost everything. But The 100 Thing Challenge is more than just the story of how one man started a movement to unhook himself from consumerism by winnowing his life's possessions down to 100 things in one year. It's also an inspiring, invigorating guide to how we all can begin to live simpler, more meaningful lives.